Seismic Vulnerability Assessment of Historical Masonry Buildings in Croatian Coastal Area - Željana Nikolić; Luka Runjić; Nives Ostojić Škomrlj; Elena Benvenuti (Applied Sciences, 2021)
(1) Background: The protection of built heritage in historic cities located in seismically active areas is of great importance for the safety of inhabitants. Systematic care and planning are necessary to detect the seismic vulnerability of buildings, in order to determine priorities in rehabilitation projects and to continuously provide funds for the reconstruction of the buildings. (2) Methods: In this study, the seismic vulnerability of the buildings in the historic center of Kaštel Kambelovac, a Croatian settlement located along the Adriatic coast, has been assessed through an approach based on the calculation of vulnerability indexes. The center consists of stone masonry buildings built between the 15th and 19th centuries. The seismic vulnerability method was derived from the Italian GNDT approach, with some modifications resulting from the specificity of the buildings in the investigated area. A new damage–vulnerability–peak ground acceleration relation was developed using the vulnerability indexes and the yield and collapse accelerations of buildings obtained through non-linear static analysis. (3) Results: A seismic vulnerability map, critical peak ground accelerations for early damage and collapse states, and damage index maps for two return periods have been predicted using the developed damage curves. (4) Conclusions: The combination of the vulnerability index method with non-linear pushover analysis is an effective tool for assessing the damage of a building stock on a territorial scale.